2020
DOI: 10.1044/2019_persp-19-00146
|View full text |Cite
|
Sign up to set email alerts
|

Telepractice for Adult Speech-Language Pathology Services: A Systematic Review

Abstract: Purpose We conducted a systematic review of the literature regarding adult telepractice services (screening, assessment, and treatment) from approximately 2014 to 2019. Method Thirty-one relevant studies were identified from a literature search, assessed for quality, and reported. Results Included studies illustrated feasibility, efficacy, diagnostic accuracy, and noninferiority of various speech-language pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
0
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(138 citation statements)
references
References 73 publications
5
93
0
17
Order By: Relevance
“…A systematic review with 31 articles regarding adult telepractice services found that about 3% correspond to voice clinical practice. 53 Although telepractice is somehow the most appropriate approach during a pandemic scenario, it may not be appropriate in all circumstances or for all conditions that the patient presents. In this sense, the eligibility for the provision of services using this modality must be well considered before starting.…”
Section: Telepractice Generalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review with 31 articles regarding adult telepractice services found that about 3% correspond to voice clinical practice. 53 Although telepractice is somehow the most appropriate approach during a pandemic scenario, it may not be appropriate in all circumstances or for all conditions that the patient presents. In this sense, the eligibility for the provision of services using this modality must be well considered before starting.…”
Section: Telepractice Generalitiesmentioning
confidence: 99%
“…Forms of telepractice may be synchronous, asynchronous, or a hybrid approach. 53 Those modalities can be used for the assessment and treatment. Synchronous methods are known as real-time interactions using telepractice between patient and clinician.…”
Section: Telepractice Generalitiesmentioning
confidence: 99%
“…2014). An acoustic speech processor may be useful for measures of loudness, pitch and duration data (Weidner and Lowman 2020); and controlling noise and microphone position can reduce random error (Jannetts et al . 2019).…”
Section: Service Delivery/clinical Implicationsmentioning
confidence: 99%
“…Telepractice is an effective service delivery model across a spectrum of disorders, including childhood speech and language disorders, 7,8 fluency disorders, 9,10 neurogenic communication disorders, [11][12][13] and dysphagia. 14,15 Most areas of speech language pathology practice have evidence supporting the use of telepractice as a model of service delivery, with adaptation using technologies, for example, the use of both synchronous and store-and-forward components.…”
mentioning
confidence: 99%